Role of responsive neurostimulation and immunotherapy in refractory epilepsy due to autoimmune encephalitis: A case report - Chen, Stephanie H.; O'Dea, Pamela K.; Sianati, Bahareh; Benavides, David R. (Frontiers in Neurology, 2022)
Autoimmune encephalitis (AE) frequently presents with seizures in the acute setting. Seizures are often refractory to anti-seizure medications (ASM) but have been shown to be responsive to immunomodulatory therapies. A subset of patients with AE continues to have refractory epilepsy, recently named “autoimmune-associated epilepsy (AAE),” for years after the acute AE presentation. Optimal treatment for AAE has not been determined. Furthermore, the efficacy of neuromodulation and immunotherapy has not been well established in AAE. Here, we report a patient with probable autoantibody negative AE who initially presented with new onset refractory status epilepticus (NORSE). After his acute presentation, he continued to have frequent seizures that were refractory to four ASMs at therapeutic doses. A responsive neurostimulation (RNS®, NeuroPace) system was implanted for diagnostic and therapeutic purposes, with minimal change in seizure frequency. Due to continued frequent seizures despite ASMs and neurostimulation, he underwent a trial of immunotherapy consisting of high-dose intravenous (IV) corticosteroids and intravenous immunoglobulin (IVIG). Despite the addition of immunotherapy to his treatment regimen, the patient experienced no significant clinical or electrographic change in seizure frequency. This case does not support the use of immunotherapy for treatment of AAE and illustrates the need for consensus guidelines in the management of patients with AAE. Further, the use of electrocorticography (ECoG) data provided an objective surrogate measure of seizure frequency; this may support the role for early neuromodulation in the management of AAE.